On Relationality and Organizationality: Degrees of durability, materiality, and communicatively constituting a fluid social collective. Issue 11 (November 2022) - Smith, William Roth
Recent organizational theorizing contends that loosely structured fluid social collectives may attain degrees of "organizationality" depending on whether or not they achieve certain organization-like elements. The organizationality approach offers a compelling account for the persistence of fluid social collectives, but the framework could be strengthened by moving beyond language-centered explanations and including into theorizing a plurality of "entities" that differ in ontological status. Based on a case study within the context of a fluid user-built recreation space, this study adopts a relational ontology viewpoint on materiality to show how dynamic aspects of natural elements, expectations, feelings, and the cyclicality of nature can be theorized as material, and thus mattering, to organizing processes. Findings reveal that the degree of durability of these entities is key for understanding interconnected decision-making, identity, and ultimately how the fluid collective achieves or degrades organizationality.